Eksistensi Ombudsman Republik Indonesia Dalam Pengawasan Terhadap Lembaga Pelayanan Publik - Ni Nyoman Wulan Prasintya Putri; I Nyoman Putu Budiartha; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2021)
Less optimal control function has been done by institutions existing oversight led to still many irregularities in the awarding of public service to the community, such fraud commonly called the behavior of maladministration. This is what inspired the creation of the Ombudsman of the Republic of Indonesia. The problem is how the Ombudsman RI authority in exercising oversight over public services organized by the State? and how is the position of Ombudsman RI in RI constitutional arrangement to achieve good governance in Indonesia ? The type of research in this thesis is the type of normative research, to approach the problem approach is the approach of legislation and conceptual approaches. The existence of the Ombudsman of the Republic of Indonesia can be seen from the implementation of the Ombudsman's supervisory function which has a good impact, this can be seen from the creation of good public services in accordance with the law and good governance. contained in the Ombudsman Law of the Republic of Indonesia Number 37 of 2008 Article 6, Article 7, and Article 8 in receiving reports of alleged maladministration.